2020
DOI: 10.1155/2020/4357910
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Clinical Features Analysis of Respiratory Adenovirus Infections Reveals Correlations between Genotype, Inflammatory Biomarkers, and Disease Severity

Abstract: Background. Human adenoviruses (HAdVs) are commonly causing respiratory disease. We molecularly genotyped HAdV circulating in Chinese hospitalized children with respiratory infections and summarized the clinical profiles and common inflammatory biomarkers, so as to better determine their associations with disease severity. Method. Children with respiratory single HAdV infection cases that occurred from December 2017 to March 2019 were enrolled for a cross-sectional study. Clinical/laboratory features based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…AdV-C (predominantly AdV-2 and -1) was the most commonly detected species in our study (70%), compared with AdV-B (22%). This finding is similar to a study in Egypt in which 75% and 22% of children under 2 years of age had AdV-C and AdV-B detected, respectively, 33 but in contrast to studies from China that reported AdV-B as the predominant species detected in hospitalized children <14 years with febrile respiratory infection symptoms 34 or hospitalized with pneumonia (92.9%), 28 and from Argentina that described 50% AdV-B detection followed by 40% AdV-C prevalence among patients seen in the ED or hospitalized. 35 These differences might be related to AdV regional circulation, different age groups, and/or species/types shifting over time.…”
Section: Discussionsupporting
confidence: 87%
“…AdV-C (predominantly AdV-2 and -1) was the most commonly detected species in our study (70%), compared with AdV-B (22%). This finding is similar to a study in Egypt in which 75% and 22% of children under 2 years of age had AdV-C and AdV-B detected, respectively, 33 but in contrast to studies from China that reported AdV-B as the predominant species detected in hospitalized children <14 years with febrile respiratory infection symptoms 34 or hospitalized with pneumonia (92.9%), 28 and from Argentina that described 50% AdV-B detection followed by 40% AdV-C prevalence among patients seen in the ED or hospitalized. 35 These differences might be related to AdV regional circulation, different age groups, and/or species/types shifting over time.…”
Section: Discussionsupporting
confidence: 87%
“…Although the sample size of this study is limited, it is similar to those of many other previously published studies analysing molecular typing for HAdV outbreaks (5,9,16,(49)(50)(51). The study samples were from pediatric patients of a private general hospital in Hanoi, Vietnam and molecular typing was performed using samples with Ct for HAdV <30.…”
Section: Discussionmentioning
confidence: 99%
“…A challenge created by COVID-19 is that no specific clinical features discern the disease from other respiratory illnesses [1]. Common methods to quantify respiratory compromise assist clinicians in planning and delivering appropriate care for people presenting with respiratory symptoms [2][3][4][5]. It is well-known, in those who are hospitalised with illness causing respiratory compromise, that the duration of the immobility and frequency of mobility during hospitalisation impact functional outcomes, exercise capacity and discharge destination [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%